Brotherhood in John Boyne’s The Boy in the Striped Pajamas - Thalib, Jannati Haytsu; Prasaja, Y.B Agung (Sintuwu Maroso Journal of English Teaching, 2023)
This study aims to analyze the brotherhood that appears in John Boyne’s The Boy in the Striped Pajamas. The objectives of this research are, to find out the forms of brotherhood in the novel entitled The Boy in the Striped Pajamas, to answer what are the implications of brotherhood in the novel entitled The Boy in the Striped Pajamas, and to analyze about what are Bruno’s motivations to grant brotherhood in the novel entitled The Boy in the Striped Pajamas. In order to analyze the brotherhood in the novel entitled The Boy in the Striped Pajamas the writer employs a qualitative descriptive method and a sociological approach of literature. The researcher applies Foubert and Schutt’s theories to examine the topic. The researcher found three findings from this research. The first is that there are four forms of brotherhood depicted in the novel entitled The Boy in the Striped Pajamas, which are brotherhood by blood, brotherhood by friendship, brotherhood of service, and brotherhood of Ideology. The second finding of this study is that there are four implications found in a novel entitled The Boy in the Striped Pajamas, for instance, emotional support, a sense of belonging, responsibility, and toughness. The last finding is Bruno's motivation to grant the brotherhood, there are five factors that cause Bruno to achieve brotherhood in the novel entitled The Boy in the Striped Pajamas, such as: experience, support, loyalty, trust, and solidarity.